Efektivitas Penyuluhan Ceramah Dan Video Dalam Meningkatkan Minat Pemeriksaan Hiv Pada Calon Pengantin Di Puskesmas Cangkringan - Neni Purnama Dewi; Siti Fadhilah; Eka Vicky Yulivantina (Nan Tongga Health And Nursing, 2026)
HIV/AIDS remains a major global and national health issue. In Indonesia, only around 70% of People Living with HIV are aware of their health status, which is still below the elimination target stated in the National Action Plan (RAN) for HIV/AIDS Prevention and Control 2020–2024. HIV testing for prospective brides and grooms is part of premarital health screening aimed at preventing HIV transmission and ensuring a healthy future generation. However, the interest of prospective couples in undergoing HIV testing is still low. The purpose of the study: To determine the effect of counseling using a combination of lecture and video on the interest of prospective brides and grooms in undergoing HIV testing. Research Methods: This quantitative research applied a one-group pretest-posttest design. A total sampling technique was used, involving 32 prospective couples registered at Puskesmas Cangkringan. The research instrument was an interest questionnaire consisting of 27 validated and reliable statements. The educational media used was an 11-minute and 30-second video about HIV testing for prospective couples. Research Results: Before counseling, interest levels were categorized as low (28.2%), moderate (59.3%), and high (12.5%). After counseling, low and moderate interests decreased to 6.3% and 31.2%, respectively, while high interest increased to 62.5%. The average interest score increased from 83.53 to 105.78. Paired Sample T-Test analysis showed a p-value of 0.01 (p < 0.05). Conclusion: Health education using a combination of lecture and video methods is effective in increasing the interest of prospective couples in undergoing HIV testing at Puskesmas Cangkringan.